CONTROL SYSTEM OF SWIMMING POOL BASED pH LEVEL, RAINFALL AND LIGHT INTENSITY - Abdullah Abdullah; Silvy Asri Ramadhani Siregar (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2020)
Swimming pools have the potential to cause health problems if not properly maintained, one of them is by maintaining the swimming pool water pH. pH is very important as a parameter of water quality, the acidity is called neutral if the pH value is 7, the value of pH <7 contains acids and pH > 7.8 contains bases. therefore designed a pool level pH control tool based on light intensity and rainfall. This tool aims to produce a neutral outdoor swimming pool water pH, able to design water pH measuring devices using light intensity sensors and rainfall sensors based on ATmega32 microcontroller and analyze the effect of swimming pool water quality on health. Tests carried out with aquarium prototype and measurements carried out for 1 day continuously. The test results show that this tool is able to neutralize the pH of swimming pool water by producing pH 6.8 and 7.1.Thus, the tool designed is efficient in providing information on the acidity of swimming pool water pH and can neutralize pH levels.